Seahorse Hotels: Use of artificial habitats to support populations of the endangered White's seahorse Hippocampus whitei. (May 2020) - Simpson, Michael; Coleman, Ross A.; Morris, Rebecca L.; Harasti, David
Abstract: The provision of temporary, specially designed artificial habitat may help support populations of the Endangered Whites' seahorse Hippocampus whitei in the face of rapid coastal urbanisation and declining natural habitats. Three designs of artificial habitat (Seahorse Hotels) were installed in Port Stephens, New South Wales, Australia, where natural habitats had significantly declined. Mark recapture surveys were used to assess seahorse site fidelity and population parameters, and the effect of Seahorse Hotel design on seahorse abundance, epibiotic growth and mobile epifaunal seahorse prey was determined. The Seahorse Hotels sustained a substantial population of seahorses (64; 57–72 95% confidence intervals) in comparison to recent local population estimates. There were no significant differences in seahorse abundance, mobile epifauna or epibiotic growth among the three different hotel designs. This research demonstrated that H. whitei will inhabit Seahorse Hotels in absence of natural habitat, and additional complexity in these artificial structures was not necessary to support seahorse populations. Temporary structures such as Seahorse Hotels will be a valuable tool in supporting H. whitei and other Syngnathid populations through infrastructure maintenance or habitat modification. Highlights: Seahorse Hotels are a temporary artificial habitat for seahorses. They are trialled here for the Endangered seahorse Hippocampus whitei . Seahorses Hotels supported a relatively large population of seahorses. Additional complexity was not necessary to support seahorses.